2021
DOI: 10.1017/bec.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction, Weight-Related Behaviours, and Health Behaviours: A Comparison Between Australian and Malaysian in Female Emerging Adults

Abstract: The presence of body dissatisfaction (BD) in non-Western countries is an important area of empirical enquiry. The results reflect collectivistic and individualistic cultures of Malaysians and Australians, respectively, whereby social approval, social acceptance, and cultural values are of high importance to Malaysians compared with the more liberal attitudes of Australians with respect to health behaviours. This study sought to compare: (1) Australian and Malaysian women on BD, thin ideal internalisation, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Several studies in recent years reported that BD was highly prevalent among Malaysian university students, which is alarming (Kamaria et al, 2016;Loke et al, 2022;Wong & Say, 2013). Supporting previous studies on university students from other regions (Barker & Galambos, 2007;Juarascio et al, 2011), recent studies on Malaysian university students suggested that BD was a salient and key risk factor for the development of DE in these emerging adults (Chin et al, 2020;Shagar et al, 2019;Shagar et al, 2021). Additionally, ethnicity may not be a significant predictor of DE among Malaysian university students, as Malaysian university students of all ethnicities may be similarly at risk for DE (Chin et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 77%
See 1 more Smart Citation
“…Several studies in recent years reported that BD was highly prevalent among Malaysian university students, which is alarming (Kamaria et al, 2016;Loke et al, 2022;Wong & Say, 2013). Supporting previous studies on university students from other regions (Barker & Galambos, 2007;Juarascio et al, 2011), recent studies on Malaysian university students suggested that BD was a salient and key risk factor for the development of DE in these emerging adults (Chin et al, 2020;Shagar et al, 2019;Shagar et al, 2021). Additionally, ethnicity may not be a significant predictor of DE among Malaysian university students, as Malaysian university students of all ethnicities may be similarly at risk for DE (Chin et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 77%
“…BD is defined as a negative subjective evaluation of one's own body (Stice & Shaw, 2002) which typically involves a discrepancy between one's ideal body and self-evaluation of own current body size and shape (Grogan, 2021). Multiple cross-cultural and crossnational studies have suggested that BD among university students might be similar and not culturally specific (Shagar et al, 2019;Shagar et al, 2021;Soh et al, 2006;Swami et al, 2010;Wardle et al, 2006). Several studies in recent years reported that BD was highly prevalent among Malaysian university students, which is alarming (Kamaria et al, 2016;Loke et al, 2022;Wong & Say, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one study, Malaysian Chinese women from urban areas of Malaysia reported greater body dissatisfaction than Australian women [ 43 ]. In another study, Australian women reported higher body dissatisfaction than Malaysian women, although effect sizes were very small [ 44 ]. Shagar and colleagues tested the tripartite model of body image in Australian and Malaysian women.…”
Section: Introductionmentioning
confidence: 99%